Short term radiological outcome of inserting screw at fracture level in posterior short segment fixation in thoracolumbar burst fractures - Pradhan, Rabindra Lal; Pandey, Bimal Kumar; Khanal, Krishna Raj (Journal of Kathmandu Medical College, 2017)
Background: Unstable thoracolumbar burst fractures are treated surgically by short segment fixation but may be associated with high implant failure. Supplementation of anterior column by insertion of screw at fracture site makes it more biomechanically stable. Objectives: The purpose of this prospective study was to evaluate radiological parameters in thoracolumbar fractures treated with intermediate screw fixation with a minimum follow up of two years. Methods: This prospective study was conducted from 2011 till 2012 where unstable thoracolumbar fractures treated with short segment posterior instrumentation with screw at fracture site were evaluated. All patients (average age 34.64 were followed up for at least 24 months and were classified according to Thoracolumbar Injury Classification and Severity Score and load sharing classifi cation. Out of total 32 patients, four lost to follow up. Radiological parameters like vertebral body height and segmental kyphosis were evaluated and pain was evaluated by Visual Analogue Scale score. Results: Preoperative pain showed mean Visual Analogue Scale Score score of 8.29 that improved to 0.97 at fi nal follow up. Average preoperative loss of vertebral body height was 48.19 %, which improved to 11.4 % after surgery (p<.001). Final vertebral body collapse was 12.98 % with mean percentage loss of vertebral height at 1.57%. Average segmental kyphotic angle was 22.54 before surgery, which corrected to 5.89 immediately after surgery (p<0.001). Final segmental kyphosis was 8.46. Loss of kyphosis correction was 2.57. Two patients had implant failure, but was solidly united during implant removal in both cases. Conclusion: Excellent maintenance of reduction in thoracolumbar burst fractures with short segment fixation with intermediate screws at fracture site with limited decompression resulted in improved neurologic function and satisfactory clinical outcomes, with a low incidence of implant failure and progressive deformity.